INSTITUTIONAL CAPACITY FOR THE DEVELOPMENT OF TEAM MANAGEMENT IN THE CIVIL SERVICE MANAGEMENT SYSTEM IN UKRAINE UNDER MARTIAL LAW - Nataliia Larina; Ihor Zbihlei (Публічне управління та регіональний розвиток)
The transformation processes taking place in Ukraine today under martial law require new approaches to the institutionalisation of the public administration system. One such approach is the principle of team building (team building) in the organisation of managerial and professional activities of civil servants. According to the author, there is a need to introduce a team-building approach to the functioning of competitive management teams in public authorities. This is due to the complexity of the tasks faced by civil servants under martial law in Ukraine and the prospects for transformational changes in public administration in the post-war period, as well as in the context of Ukraine's integration processes into the European community. Such challenges in the organisation of management activities of civil servants require a combination of intellectual and volitional efforts of the authorities to dynamically solve various management tasks, which cannot be implemented without the creation of target (project) groups and high competition between different authorities. This requires managers to provide client-oriented administrative services, increase the competitiveness of civil servants and the authorities themselves.